THE JUNGLE BOOK - RUDYARD KIPLING (COLLINS UK, 2013)
"The Jungle Book," a classic collection of stories by Rudyard Kipling, follows the adventures of Mowgli, a young boy raised by wolves in the Indian jungle. Through a series of tales, Mowgli encounters a diverse cast of animal characters, including the wise bear Baloo, the cunning tiger Shere Khan, and the pragmatic panther Bagheera. As Mowgli grows up, he grapples with his identity and place within the jungle, navigating the complexities of both animal and human worlds. The book explores themes of belonging, self-discovery, and the laws of nature, blending vibrant storytelling with profound moral lessons.